Peran Pengelolaan Dan Pengendalian Risiko Dalam Lembaga Pendidikan - Putri Chayu Ningsih; Irsyad, Irsyad; Merika Setiawati (CV. ITTC INDONESIA, 2025)
Risk is an inseparable part of human life, including in the field of education. Risk management in the education sector plays a crucial role in ensuring the continuity and quality of teaching and learning processes. This study examines the concept of risk management in education, covering risk identification, analysis, mitigation planning, implementation, and risk evaluation within the context of educational institutions. A literature review indicates that well-planned risk control strategies help educational institutions address various internal and external challenges, maintain educational quality, enhance operational effectiveness, and ensure the safety of students and staff. The effective implementation of risk management also strengthens institutional resilience in facing change and disruption, while minimizing the negative impacts of risks on the quality and sustainability of education.